A relação das categorias pluralismo e ecletismo Epistemológico com a produção do conhecimento na história da educação - Silva, Maria das Graças Miranda Ferreira da (2015)
This thesis, entitled The Relationship of the Categories Pluralism and Eclecticism Epistemological with the Production of Knowledge in the History of Education, aimed to analyze the study’s overall production of knowledge in the area of postgraduate education – Stricto Sensu – in the Federal University of Paraíba, specifically in the line of research in History of Education, Postgraduate Program in Education, in the light of the Pluralism and Eclecticism categories in their epistemological dimensions. All this considering the dilemmas present in social knowledge and in education as the result of the crises that permeated the societies and the humanities and social sciences. The kind of research set up of dialectical and plural types, of theoretical character and with a predominantly qualitative analysis approach, through the use of bibliographic and documentary research, as investigative processes around the production of knowledge in the field of history of education of the Postgraduate Program in Education of UFPB. Accordingly, the source of documentary research were the theses and dissertations in the line of research in History of Education on the said Postgraduate Program. Ten theses and forty-three dissertations were found on the collection of Digital Library of Theses and Dissertations of UFPB and on Education Sector Library of the Center of Education of UFPB, during the period of 2009 to 2014. Period in which was possible have access to the firsts theses defended on the Doctorate of the said Program since this Doctoral Course only began in the year of 2003 on UFPB. Authors like Carlos Nelson Coutinho, Dermeval Saviani, François Dosse, Luciano Mendes de Faria Filho, Diana Gonçalves Vidal and others have been worked on this Thesis. Among the results of the research we found that the paradigm of subjectivity has prevailed in the line of research in History of Education as well as the epistemological idealists bases. This is confirmed by the very high presence, in this line of research, of the interpretative array of the New Cultural History that is permeated by the defended characteristics in the said social paradigm. However, others interpretative currents also live in the said line of research, and we also found that although the predominance of this matrix of the New Cultural History, there is an opening to the Epistemological Pluralism that we defend in this thesis. We conclude that this Pluralism defended in this work is not confused with fragmentation of knowledge, since it is not mere diversity, but rather a diversity containing a conducting yarn that makes it cohesive and articulate. This conducting yarn concerns the search for the approximation to reality perspective, and this is true of analysis contextualized, analysis that interrelate micro and macro realities, dialectically, analysis that emphasize the interaction between subjective and objective aspects. Therefore, in this way, the pluralism can experience the unity in the diversity, reaching a dialectical synthesis. Keywords: Epistemological Pluralism. Eclecticism Epistemological. History of Education. Production of knowledge.